Meta-aggregation of facilitators and barriers to home-based palliative care - Zixuan Liu; Hui Zhang; Yuxuan Zhang; Yuqing Dai; Yu Sheng (BMC Palliative Care)
Abstract Background Home-based palliative care is in the early stages of development, and its implementation continues to face numerous challenges. Objective This study aims to systematically synthesize qualitative research on the facilitators and barriers to home-based palliative care, offering evidence-based recommendations to support the advancement of palliative care in China. Methods A systematic search was conducted across multiple databases including PubMed, Web of Science, Embase, Cochrane Library, CINAHL, CNKI, Wanfang,2222 and VIP Database for qualitative studies related to home-based palliative care, with the search covering studies published up to October 3, 2024. Quality assessment was performed using the JBI standards for qualitative research. Meta-Aggregation was performed using an aggregative integration approach, and the data were analyzed and managed using Nvivo software. Conclusions Twelve studies involving 334 participants were included. Ninety-nine initial findings were extracted and categorized into eight groups. Facilitators included family support, collaboration within interdisciplinary teams, and community resource availability. Barriers comprised challenges in healthcare policies, cultural and social influences, lack of Knowledge and Attitudes of Healthcare Workers, lack of Knowledge and Attitudes of Patients and Families, and insufficient home care resources. Conclusion To advance palliative care in China, it is critical to enhance policy support and financial backing, improve the education and training of healthcare professionals and the public in diverse cultural settings, strengthen community nursing capabilities, and explore the integration of information technology in care delivery.